Nursing management in allogeneic hematopoietic stem cell transplantation for children with Fanconi anemia (范可尼贫血患儿行异基因造血干细胞移植术的护理) - WANG Yu (王宇); LIU Xiaolin (刘晓琳); LIN Le (林乐); JI Ling (纪玲); ZHANG Le (张乐); ZONG Panpan (宗盼盼); XU Xiaodong (徐晓东) (中西医结合护理)
This paper reviewed the clinical data of 15 children undergoing allogeneic hematopoietic stem cell transplantation (HSCT) for Fanconi anemia. All the children received comprehensive nursing measures including overall environmental protection, infection prevention, safety protection, psychological counseling and health education based on their disease characteristics and disease progression. Allogeneic hematopoietic stem cell transplantation was successfully performed in 15 children with Fankone anemia. After transplantation, the mean time of neutrophil engraftment was (11. 67±1. 67) d, time of transferred out of laminar flow room was (13. 33±1. 49) d. (本文回顾了科室科收治的行异基因造血干细胞移植术治疗的范可尼贫血患儿15例的临床资料。结合患儿的疾病特点与病情进展, 为患儿实施全环境保护、预防感染、安全防护、心理疏导和健康教育。15例范可尼贫血患儿成功进行异基因造血干细胞移植, 于移植后平均(11. 67±1. 67)d中性粒细胞开始重建, 平均(13. 33±1. 49)d转出层流室。)